Pentingnya Kompetensi Pedagogik dalam Pembelajaran Berbasis Teknologi Informasi - Alfina; Yana Ayu Andini, Dwi (Universitas Aisyah Pringsewu, 2022)
The learning process uses interactive digital-based information technology that can improve thequality of learning, making it easier for students and educators to interact in the learningprocess. Giving assignments to students can support the activity of repeating students' subjectmatter at home, but the ability to understand pedagogy and the role of the teacher in deliveringmaterial to students is no less important. This type of research used qualitative descriptionsobtained from Information Technology Education students who took learning evaluationlectures. The data collection instrument was obtained from a questionnaire that had beendistributed to Information Technology Education students. The digital learning process can becarried out with information technology-based learning, so that learning becomes conduciveand dynamic. One of the learning concepts is to use learning strategies that are carried out byapplying information technology-based pedagogic methods. To make learning conducive anddynamic, 3 learning strategies are applied, namely: (1) using pedagogic methods appropriatelyand correctly by educators; (2) increasing collaboration or collaboration between educatorsand students; (3) apply and utilize information technology in learning.